Analisis pengendalian kualitas produk roti menggunakan metode taguchi pada UMKM Roti Masempo - Safitri, Rindiani; Wolok, Eduart; Lahay, Idham Halid (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to improve the quality of bread products at UMKM Roti Masempo using the Taguchi method. The aim of the research was to investigate the main causes of defects in bread products and determine the optimal combination of process parameters to reduce defect rates. The Taguchi method was applied with the